Pengembangan Sistem Informasi Aspirasi Online Berbasis Web Menggunakan Pemodelan Reuse-Oriented Development (Studi Kasus : DPM Universitas Brawijaya) - Ali Fikri; Ismiarta Aknuranda; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
As a legislative institution, DPM UB has a function to advocate for aspirations delivered by students or other institutions in the structure of LKM UB. However, the lack of service delivery and absorption of aspirations that were implemented resulted in a lack of aspirations received, resulting in an underperformance of the organization. To make it happen, it is necessary to implement good student governance in order to optimize the services provided. Based on these problems, an information technology instrument is needed, namely by developing an online aspiration information system. The approach method used is a reuse-oriented development model to obtain higher quality and productivity during the development process. The steps taken in the study are literature studies, business process modeling, requirements analysis, component analysis, requirements modification, design using components, implementation, testing and analysis. For system development purposes, were produced 2 as-is business process models, 1 to-be business process model, and generate 10 use-case system. The system validation test results stated 100% valid, the average results of compatibility tests were 89%, the results of user acceptance tests were 81%, and the results of the time efficiency test were 84.4%. So from these results, it can be concluded that the use of information technology developed using reuse-oriented methods can be accepted and have a positive impact on LKM UB.